Antibiotic Susceptibility Profile for the US Neisseria meningitidis Urethritis Clade. (12th December 2022) - Bazan, Jose A; Tzeng, Yih-Ling; Bischof, Katarina M; Satola, Sarah W; Stephens, David S; Edwards, Jennifer L; Carter, Alexandria; Snyder, Brandon; Turner, Abigail Norris
Abstract: The US Neisseria meningitidis urethritis clade (US_NmUC) harbors gonococcal deoxyribonucleic acid alleles and causes gonorrhea-like urogenital tract disease. A large convenience sample of US_NmUC isolates ( N = 122) collected between January 2015 and December 2019 in Columbus, Ohio demonstrated uniform susceptibility to antibiotics recommended for gonorrhea treatment and meningococcal chemoprophylaxis. Abstract : Antibiotic susceptibility testing of a large convenience sample of United States Neisseria meningitidis urethritis clade (US_NmUC) isolates collected between 2015 and 2019 in Columbus, Ohio, demonstrated uniform susceptibility to antibiotics recommended for gonorrhea treatment and meningococcal chemoprophylaxis.